A rare case of syringocystadenoma papilliferum: clinical and histopathological insights - Andayani, Raden Roro Rini; Pudjiati, Satiti Retno; Harsono, Erliana Tantri; Rizkiani, Dwinanda Almira; Hanggoro Tri Rinonce; Rita Cempaka; Indra Wahono; Siti Isya Wahdini; Dyah Ayu Mira Oktarina (Published by Universitas Gadjah Mada, 2025)
Syringocystadenoma papilliferum (SCAP) is a rare benign adnexal neoplasm originating from apocrine or eccrine sweat glands, first reported by Stokes in 1917. Clinically, SCAP manifests in various forms such as nodules, plaques, or warts, predominantly affecting the scalp in adolescents or children. Histopathologically, it is characterized by papillary and ductal invaginations lined with a two-layered epithelium. This condition can be present at birth or emerge during puberty. We present a 19-year-old female with a congenital, pinkish-brown, wart-like lesion on her scalp that progressively enlarged and spread to the face. Physical examination revealed a verrucous plaque with central erosion, extending from the temporal scalp to the lateral face. Dermoscopy showed papillary structures with defined lesion borders, while histopathological findings confirmed SCAP. The patient underwent surgical excision, and no new lesions were detected during a 3 mo follow-up. Syringocystadenoma papilliferum is often confused with other neoplasms such as sebaceous nevus or verruca vulgaris, but its definitive diagnosis relies on histopathology. The tumor’s characteristic features include cystic invaginations into the dermis with a two-layered epithelium, differentiating it from other conditions. Surgical excision remains the treatment of choice to prevent potential malignant transformation and improve cosmetic outcomes. Syringocystadenoma papilliferum, though rare, can be effectively managed through timely diagnosis and surgical excision. In this case, the patient’s postoperative outcome was favorable, with no recurrence of the lesion. Histopathological evaluation is crucial for accurate diagnosis and guiding treatment strategies.